The Role of Scripture at and Around the Council of Nicaea - Folan, Peter M. (2025)
This article argues that the Council of Nicaea, which has borne responsibility for moving the church away from a primarily scriptural mode of speaking, is, in fact, thoroughly grounded in what we might call “the symbolic universe of Scripture.” The events and documents that preceded, were contemporaneous with, and followed Nicaea all chart their own ways through that universe, even when they appear to have departed it. Today, the council beckons and helps guide the church, in particular its theologians, to live again in the world that Scripture produces.
Keywords: Scripture; Imagination; Creed; Council of Nicaea; Bible; Arius